2021
DOI: 10.1371/journal.pone.0260409
|View full text |Cite
|
Sign up to set email alerts
|

Examining potential gender bias in automated-job alerts in the Spanish market

Abstract: Numerous field experiments based on the correspondence testing procedure have documented that gender bias influences personnel selection processes. Nowadays, algorithms and job platforms are used for personnel selection processes because of their supposed neutrality, efficiency, and costs savings. However, previous research has shown that algorithms can exhibit and even amplify gender bias. The present research aimed to explore a possible gender bias in automated-job alerts generated in InfoJobs, a popular job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The analysis of this study showed that there is indeed a significant gender bias in job listings, where the use of a large number of gender keywords drives a significant amount of bias, and that the technical bias present in such algorithms has a higher impact and influence on the hiring decisions of female users applying for specific positions. Secondly, as another study mentioned [3], researchers aimed at exploring the automated job alerts generated in InfoJobs, a popular Spanish employment platform. Researchers similarly confirmed the presence of gender bias in such job recruitment platforms and its negative impact on female personnel in the selection process through a corresponding testing procedure.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of this study showed that there is indeed a significant gender bias in job listings, where the use of a large number of gender keywords drives a significant amount of bias, and that the technical bias present in such algorithms has a higher impact and influence on the hiring decisions of female users applying for specific positions. Secondly, as another study mentioned [3], researchers aimed at exploring the automated job alerts generated in InfoJobs, a popular Spanish employment platform. Researchers similarly confirmed the presence of gender bias in such job recruitment platforms and its negative impact on female personnel in the selection process through a corresponding testing procedure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To manage the overwhelming number of applicants, Amazon developed an AI-powered automated hiring tool in 2014 that used algorithms to review resumes and select candidates. It may sound like the emergence of this technology has brought well-being to people, based on the popular belief that the machine algorithms used for the worker selection process that have emerged in today's workplaces are more supposedly neutral, efficient, and cost saving compared to humans [3]. However, the Amazon AI-powered automated hiring tool raises gender bias, a very serious ethical problem, which limits the opportunities for women's employment in the Information Technology field.…”
Section: Introductionmentioning
confidence: 99%
“…Governments have adapted ICT4D into their policies to empower citizens 43 . Researchers have also conducted feminist science and technology studies to propose ways to empower women's social presence using ICT4D 44 , 45 . For example, some studies show that ICT can contribute to economic well-being and empower women's community building and political organization 46 .…”
Section: Can Ai Improve Gender Equality In Afghanistan?mentioning
confidence: 99%